Black ex-model-C school learners’ experiences of racial microaggressions - Canham, Toni Misty Kyla (Department of Psychology, 2019)
In post-Apartheid South Africa, the ongoing salience of race has proved problematic, with many of these racial disputes being circulated widely on social media platforms. Much focus, energy, and emotional investment in these instances of overt racism, against which South Africa still struggles, exemplify the racialized society we live in today. While these instances of explicit racism are heavily focused on, more subtle forms of racism seem to go unnoticed in our day-to-day lives. These subtle forms of racism are called racial microaggressions. Operating within a social constructionist framework, this qualitative study utilized purposive sampling to investigate racial microaggressions experienced by Black1 participants from previously Model-C schools. The focus groups conducted were analysed by means of a thematic analysis, which yielded eight main themes, namely, the second-class citizen; patronizing ascriptions of intelligence; #HandsOffMyCrown; the invisibilization of race andprivilege; morphing bigotry or innocent preference?; under-representations of Black staff and learners; cultural assimilation; and knowledge in the blood. While some of these findings coincide with themes from American and European research (for example, patronizing ascriptions of intelligence, the invisibilization of race and privilege, and the second-class citizen), certain themes appear to be unique to the South African setting. Studies should ideally be carried out across historically white high schools around South Africa to obtain a more representative sample from which to collect data.